PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA MELALUI MEDIA KIT DI KELAS VI SEKOLAH DASAR NEGERI 08 BONDAU KECAMATAN MENUKUNG KABUPATEN MELAWI TAHUN AJARAN 2012-2013 - Selfinus Selfinus; Sugiatno Sugiatno; Yakobus Ason (JURNAL PENDIDIKAN DASAR, 2014)
The purpose of this research is to increase the student learning result on the subject mathematic, especially by implemented the KIT media on the learning process. The method used in this research was the class action research, where the subject of the research its self was the 25 students of grade VI Public Elementary School No.08 Bondau. The students were including 11 male students and 14 female students. The result of this research shown there was increasing in learning process by using KIT media over the subject mathematic. The class average grade in the first cycle was 66.30, and 83.90 in the second cycle. The increasing of student learning result from 1st cycle to 2nd cycle was 17.60. Keywords: Study Result, Learning on Mathematic Subject, KIT Media